The "Tabola-Bale" Bureaucracy (Analysis of the Dynamics of State Institutions in Indonesia) - Bakri, Riani; Utami, Fadilah Risqy; Husain, Fachril (Jurnal Pallangga Praja (JPP), 2025)
The dynamics of state institutions in Indonesia are interesting to study. The change from an Agency to a Ministry or from a Ministry to an Agency is part of the dynamics of state institutions. This article aims to examine the dynamics of state institutions as an instrument of government, using a descriptive qualitative analysis approach. To support governance, the government requires government instruments, including government facilities/infrastructure, institutions, and policy instruments. Government instruments are the tools or means used by the government or government administration in carrying out its duties. As a welfare state that governs its people from upstream to downstream, the dynamics of state institutions are unavoidable in the context of accelerating certain government affairs, both technical and functional.